Orthognathic Surgery: General Considerations - Khechoyan, David Y. (Seminars in Plastic Surgery, 2013)
Orthognathic surgery is a unique endeavor in facial surgery: a patient's appearance and occlusal function can be improved significantly, impacting the patient's sense of self and well-being. Successful outcomes in modern orthognathic surgery rely on close collaboration between the surgeon and the orthodontist across all stages of treatment, from preoperative planning to finalization of occlusion. Virtual computer planning promotes a more accurate analysis of dentofacial deformity and preoperative planning. It is also an invaluable aid in providing comprehensive patient education.In this article, the author describes the general surgical principles that underlie orthognathic surgery, highlighting the sequence of treatment, preoperative analysis of dentofacial deformity, surgical execution of the treatment plan, and possible complications.
Keywords: orthognathic surgery; dentofacial deformity; malocclusion